The burden and management of anemia in Greek patients with inflammatory bowel disease: a retrospective, multicenter, observational study - Foteinogiannopoulou, Kalliopi (BMC Gastroenterol, 2021)
BACKGROUND: Anemia is a common extraintestinal manifestation of Inflammatory Bowel Disease (IBD) affecting negatively the patients’ quality of life. The aim of this study was to determine the frequency and real-life management of anemia in IBD patients in Greece. METHODS: This study was conducted in 17 Greek IBD referral centers. Demographic, clinical, laboratory, IBD and anemia treatment data were collected and analyzed retrospectively. RESULTS: A total of 1394 IBD patients [560 ulcerative colitis (UC), 834 Crohn’s disease (CD)] were enrolled. Anemia at any time was reported in 687 (49.3%) patients of whom 413 (29.6%) had episodic and 274 (19.7%) had recurrent/persistent anemia. Anemia was diagnosed before IBD in 45 (6.5%), along with IBD in 269 (39.2%) and after IBD in 373 (54.3%) patients. In the multivariate analysis the presence of extraintestinal manifestations (p = 0.0008), IBD duration (p = 0.026), IBD related surgeries and hospitalizations (p = 0.026 and p = 0.004 accordingly) were risk factors of recurrent/persistent anemia. Serum ferritin was measured in 839 (60.2%) IBD patients. Among anemic patients, 535 (77.9%) received treatment. Iron supplementation was administered in 485 (90.6%) patients, oral in 142 (29.3%) and intravenous in 393 (81%). CONCLUSIONS: The frequency of anemia in IBD patients, followed at Greek referral centers, is approximately 50%. Development of recurrent/persistent anemia may be observed in 20% of cases and is independently associated with the presence of extraintestinal manifestations, IBD duration, IBD related surgeries and hospitalizations. Anemia treatment is administered in up to [Formula: see text] of anemia IBD patients with the majority of them receiving iron intravenously.